CONCEPTUAL APPROACH TO SOLVING MANAGEMENT PROBLEMS OF THE UNIVERSITY - M. O. Shevchenko (Вестник университета, 2020)
Conceptual approach to the search for sound solutions in the field of university management has been proposed. The concept of “typical control concept” has been introduced. The procedure for creating a platform for solving management problems from university practice has been suggested. Special manipulative entity as a tool for an effective approach to the implementation of university management tasks has been determined. It has been shown what digital technologies can be used to implement certain management functions. Operands of the posed problem at the initial stage of her research determined three sets: set of management functions, set of digital technologies, set of concepts. The matrix of the relationship between digital economy technologies and basic management functions has been given. Disintegrative approach to transforming university management tasks into chains of basic management functions for the use of typical management concepts has been proposed. The directions of actual work within the framework of this research have been outlined.